Changes in dermal structure and skin oxidative stress in overweight and obese Japanese males after weight loss: a longitudinal observation study. Issue 3 (27th January 2018) - Matsumoto, M.; Ogai, K.; Aoki, M.; Urai, T.; Yokogawa, M.; Tawara, M.; Kobayashi, M.; Minematsu, T.; Sanada, H.; Sugama, J.
Abstract: Background/Purpose: Previous studies have reported decreased dermal echogenicity and increased skin oxidative stress in overweight males. However, it is unknown whether these skin parameters of overweight and obese people are similar to those of individuals exhibiting a normal body weight following weight loss. The purpose of this study was to (1) compare the changes in the dermal structure parameters and levels of skin oxidative stress before and after weight loss in overweight and obese people in Japan and (2) to clarify how these aspects changed when body weight would be reduced to normal body weight. Methods: Male volunteers with a body mass index of ≥25 kg/m 2 were recruited. The dermal structure was visualized and dermal echogenicity and thickness were measured using ultrasound scanners. The mRNA expression level of heme oxygenase‐1 in the hair follicles was quantitatively analyzed as a marker of skin oxidative stress. Results: When overweight individuals in their 20s to 30s reduced their weight to normal, decreased dermal thickness in the abdominal region was observed in 50% of the subjects; however, no increase in dermal echogenicity was observed. A decrease in dermal thickness and an increase in dermal echogenicity in the thighs was observed in 83.3% of the subjects. No decrease in the level of dermal oxidative stress was observed. Conclusion: The dermal structure in the thighs of overweight young individuals can be improved to the level of the structure in those of normal body weight individuals following weight loss.